2015
DOI: 10.17531/ein.2015.4.19
|View full text |Cite
|
Sign up to set email alerts
|

Reliability analysis of gear transmission with considering failure correlation

Abstract: Reliability analysis of gear transmission with considering failure correlation. Eksploatacja i niezawodnosc - Maintenance and Reliability 2015; 17 (4): 617-623, http://dx.doi.org/10.17531/ein.2015.4.19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The aim of numerical analysis was to predict strength of material and to shorten the time needed for experimental material testing. The numerical study shown to be very reliable for some similar testings such as welded joints [11], bucket wheel boom hoist system [12], some composite materials [13] or even transmission gears [14] and beams [15]. Also, some interesting findings on this steel can be found in research of properties of HSS S690 at low temperatures [16].…”
mentioning
confidence: 65%
“…The aim of numerical analysis was to predict strength of material and to shorten the time needed for experimental material testing. The numerical study shown to be very reliable for some similar testings such as welded joints [11], bucket wheel boom hoist system [12], some composite materials [13] or even transmission gears [14] and beams [15]. Also, some interesting findings on this steel can be found in research of properties of HSS S690 at low temperatures [16].…”
mentioning
confidence: 65%
“…This theory can decompose a joint distribution function into a Copula function and k marginal distribution [15,27]. In addition, this theory follows the Sklar theorem:…”
Section: Reliability Model Based On Failure Rate Correlation Subsystemmentioning
confidence: 99%
“…Therefore, the probability that both of the teeth survive to a load action does not equal to the product of the probabilities that the individual teeth survive to the load action respectively. Without the assumption of independent component (tooth) failures, the probability that a tooth-pair survives n times of load action under the load history i equals to 12 (…”
Section: Reliability Modeling Of Gear Transmission System Under Variamentioning
confidence: 99%
“…For instance, stress-strength interference analysis method was applied to calculate gear transmission system reliability, implying that a gear is equivalent to a component [11][12][13][14] and only one tooth is considered for gear reliability estimation [15][16][17] . In fact, simplification has long been the common practice for complex system reliability analysis, though variety of errors may be brought about.…”
mentioning
confidence: 99%